An Aspect-Oriented Approach for Spatial Concerns in Web Applications - Urbieta, Mario Matías (2013)
The growing availability of on-line geographical information, since the advent of open map servers in the 2000s, originated a new generation of Web applications, those which combine “conventional” Web functionality with typical features of traditional Geographic Application System (GIS). The rapid growth in number and complexity of Web applications with geo-referenced data together with the need to support fast requirements change, demands for increased modularity. The volatility of some of these changing requirements, both in the scope of their geographic nature or in the period of time in which they are valid, stresses the importance of the applications’ modularity. A solution is to take into consideration the crosscutting nature of these requirements and decouple their realization from “conventional” requirements in separate software modules. This paper proposes an end-to-end Aspect-Oriented approach to deal with spatial requirements from the early stages of applications development throughout to implementation. A significant contribution of this approach is the characterization of the most common spatial requirements in Web-GIS applications. The result is the improvement of the overall application’s modularity, thus facilitating its evolution.